Effect of Admission Hyperglycemia on Short-Term Prognosis of Patients with Non-ST Elevation Acute Coronary Syndrome without Diabetes Mellitus - Wei Liu; Zhijuan Li; Shiying Xing; Yanwei Xu (Journal of Diabetes Research)
Objective. To evaluate the effect of admission hyperglycemia on the short-term prognosis of patients with non-ST elevation acute coronary syndrome (NSTE-ACS) without diabetes mellitus. Methods. The clinical data of 498 patients with NSTE-ACS admitted to the Department of Cardiology of the First Affiliated Hospital of Henan University of Science and Technology between March 2018 and November 2020 were analyzed. Based on the blood glucose (BG) level at admission, patients were divided into three groups: A (BG<7.8 mmol/L), B (7.8 mmol/L≤BG<11.1 mmol/L), and C (BG≥11.1 mmol/L). The clinical data of the three groups were compared. Results. There was no significant difference between the three groups in terms of age, sex, hypertension, hyperlipidemia, smoking, and history of myocardial infarction (p>0.05). However, there were significant differences in the incidences of multivessel disease, renal insufficiency, pump failure, and emergency percutaneous coronary intervention, and levels of high-sensitivity C-reactive protein, cardiac troponin T, and creatine kinase isoenzyme MB among the three groups (p<0.05 for all). The incidences of severe pump failure, malignant arrhythmias, and death were significantly higher in groups B and C compared to group A (p<0.05). Additionally, the incidences of severe pump failure, malignant arrhythmias, and death were significantly higher in group C compared to group B (p<0.05). Multivariate logistic regression analysis showed that hyperglycemia, renal insufficiency, Killip grade III/IV, and age were risk factors of in-hospital death. Conclusion. Hyperglycemia at admission is a risk factor for adverse in-hospital clinical outcomes in patients with NSTE-ACS.